Effects of feeding two microbial additives in sequence on growth performance and carcass characteristics of finishing heifers - Huck, G.L.; Kreikemeier, K.K.; Ducharme, G.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four hundred fifty heifers (846 lb) were used in a 126-day experiment to investigate the effects of feeding two microbial additives, Lactobacillus acidophilus BG2FO4 (MicroCell) and Propionibacterium freudenreichii P-63 (MicroCell PB), alone or in sequence, on feedlot growth performance and carcass characteristics. A 21-day step-up period preceded heifers being placed on a final finishing diet containing 10% corn silage, 42% steam-flaked corn, 42% high-moisture corn, 3% soybean meal, and 3% mineral supplement. Premeasured amounts of microbial additive were mixed with water before being mixed directly with the total ration. Treatments consisted of 1) no microbial additive; 2) MicroCell for the entire period; 3) MicroCell PB for the entire period; 4) MicroCell for 28 days then MicroCell PB for the remainder of the period; and 5) MicroCell PB for 28 days then MicroCell for the remainder of the period. Feeding MicroCell for 28 days and then MicroCell PB for the remainder of the feeding period resulted in significant improvements (P<.10) in daily gain and feed efficiency.
Keywords: Beef; Lactobacillus acidophilus; Propionibacterium freudenreichii; Microbial feed additives; Finishing; Carcass